Three-dimensional motions in the Sculptor dwarf galaxy as a glimpse of a new era. (February 2018) - Massari, D.; Breddels, M.; Helmi, A.; Posti, L.; Brown, A.; Tolstoy, E.
Abstract The three-dimensional motions of stars in small galaxies beyond our own are minute, yet they are crucial for understanding the nature of gravity and dark matter1, 2 . Even for the dwarf galaxy Sculptor—one of the best-studied systems, which is inferred to be strongly dark matter dominated3, 4 —there are conflicting reports5–7 on its mean motion around the Milky Way, and the three-dimensional internal motions of its stars have never been measured. Here, we present precise proper motions of Sculptor's stars based on data from the Gaia mission8 and Hubble Space Telescope. Our measurements show that Sculptor moves around the Milky Way on a high-inclination elongated orbit that takes it much further out than previously thought. For Sculptor's internal velocity dispersions, we findσ R = 11.5 ± 4.3 km s−1 andσ T = 8.5 ± 3.2 km s−1 along the projected radial and tangential directions. Thus, the stars in our sample move preferentially on radial orbits as quantified by the anisotropy parameter, which we find to be β 0.86_-0.83^+0.12 β 0.8 6 - 0.83 + 0.12 at a location beyond the core radius. Taken at face value, this high radial anisotropy requires abandoning conventional models9 for Sculptor's mass distribution. Our sample is dominated by metal-rich stars and for these we find β ^MR 0.95_-0.27^+0.04 β M R 0.9 5 - 0.27 + 0.04 —a value consistent with multi-component spherical models where Sculptor is embedded in a cuspy dark halo10, as might be expected for cold dark matter. Precise proper motions of Sculptor's stars based on Gaia and the Hubble Space Telescope show that Sculptor moves on a high-inclination elongated orbit around the Milky Way and require abandoning conventional models for Sculptor's mass distribution.